Decision-making and attention deficit hyperactivity disorder: neuroeconomic perspective - Chachar, Aisha Sanober; Shaikh, Mahnoor Yousif (Frontiers in Neuroscience, 2024)
The decision-making process involves various cognitive procedures influenced by the interplay between cognition, motivation, and attention, forming a complex neural framework. Attention is a fundamental cognitive element within decision-making mechanisms, and one of the conditions affecting the attentional system is attention deficit hyperactivity disorder (ADHD). Decision-making impairments in ADHD have significant economic consequences, necessitating effective policies and interventions to address this critical issue. Research from computational models and neuroscience suggests how cognitive functions' workings and problems affect decision-making and provide insights into the neural implications of decision-making. This article explores the intersection of decisionmaking, ADHD, and neuroeconomics, highlighting research gaps, potential contributions, and implications for future policies.